Spatial configuration and street crime incidences in the central business district (CDB) of Johor Bahru City Centre - 492330 Kuah, Peik Khee; Chau, Loon Wai, supervisor; Fakulti Alam Bina (2010)
Project Paper (Sarjana Muda (Perancangan Bandar dan Wilayah)) -Universiti Teknologi Malaysia, 2010